A community-based healthcare package combining testing and prevention tools, including pre-exposure prophylaxis (PrEP), immediate HIV treatment, management of hepatitis B virus, and sexual and reproductive health (SRH), targeting female sex workers (FSWs) in Côte d'Ivoire: the ANRS 12381 PRINCESSE project - Valentine Becquet; Marcellin Nouaman; Mélanie Plazy; Aline Agoua; Clémence Zébago; Hervé Dao; Alice Montoyo; Aude Jary; Patrick A. Coffie; Serge Eholié; Joseph Larmarange; and the ANRS 12381 PRINCESSE team (BMC, 2021)
Abstract Background Pre-exposure prophylaxis (PrEP) is recommended by the WHO for HIV prevention among female sex workers (FSWs). A study conducted in 2016-2017 in Côte d'Ivoire showed that if PrEP is acceptable, FSWs also have many uncovered sexual health needs. Based on this evidence, the ANRS 12381 PRINCESSE project was developed in collaboration with a community-based organization. The main objective is to develop, document, and analyze a comprehensive sexual and reproductive healthcare package among FSWs in Côte d'Ivoire. Methods PRINCESSE is an open, single-arm interventional cohort of 500 FSWs in San Pedro (Côte d'Ivoire) and its surroundings. Recruitment started on November 26th, 2019 and is ongoing; the cohort is planned to last at least 30 months. The healthcare package (including HIV, hepatitis B, and sexually transmitted infection management, pregnancy screening, and contraception) is available both at mobile clinics organized for a quarterly follow-up (10 intervention sites, each site being visited every two weeks) and at a fixed clinic. Four waves of data collection were implemented: (i) clinical and safety data; (ii) socio-behavioral questionnaires; (iii) biological data; and (iv) in-depth interviews with female participants. Four additional waves of data collection are scheduled outside the cohort itself: (i) the medical and activity records of Aprosam for the PRINCESSE participants; (ii) the medical records of HIV+ FSW patients not participating in the PRINCESSE cohort, and routinely examined by Aprosam; (iii) in-depth interviews with key informants in the FSW community; and (iv) in-depth interviews with PRINCESSE follow-up actors. Discussion The PRINCESSE project is one of the first interventions offering HIV oral PrEP as part of a more global sexual healthcare package targeting both HIV- and HIV+ women. Second, STIs and viral hepatitis B care were offered to all participants, regardless of their willingness to use PrEP. Another innovation is the implementation of mobile clinics for chronic/quarterly care. In terms of research, PRINCESSE is a comprehensive, interdisciplinary project combining clinical, biological, epidemiological, and social specific objectives and outcomes to document the operational challenges of a multidisease program in real-life conditions. Trial registration The PRINCESSE project was registered on the Clinicaltrial.gov website ( NCT03985085 ) on June 13, 2019.